The determinants of bank default risk: Evidences from Vietnamese commercial banks - Vu, Bich Ngoc (2017)
This study aims to measure default risk of Vietnamese commercial banks and determine its drivers. The proxy for default risk is market-based distance to default following option pricing method of Black and Scholes (1973) and the structural method of Merton (1974). The average distance to default of all sample banks fluctuated with an increasing tendency during the research period. Using quarterly data of 9 public listed commercial banks in Vietnam in the period from 2009 to 2016 and static panel data model, credit growth, customer deposits and loan loss provisions are found to have significant effects on distance on default while return on average assets, capital adequacy and GDP growth have little impact. For comparison purpose, Boyd and Graham’s (1986) Z-Score is calculated and found to be significantly influenced by return on average assets, credit growth and customer deposits. Loan loss provisions, capital adequacy and GDP growth are not significantly correlated with Z-Score. Keywords: bank default risk, bank stability, distance to default, Z-Score, Vietnam